IMPLEMENTASI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KABUPATEN OGAN KOMERING ULU - Eva Susanti; Ikang Putra Anggara; Wahyu Agil Wijaya (JURNAL DINAMIKA, 2022)
The City Without Slums Program (Kotaku) is a program of the Kementrian Pekerjaan Umum dan Perumahan that aims to eradicate the slum areas of the closest urban village to the city, this program has the aim of creating a clean, safe and comfortable area in accordance with the 1945 Constitution article 28H paragraph 1 states that "Everyone has the right to live in physical and spiritual prosperity, to have a place to live, and to have a good and healthy living environment and have the right to obtain health services. The method used is descriptive qualitative which is based on the stages of The implementation of the Kotaku program is Planning, Site Survey, Funding, and Implementation and is related to Edward III's theory, namely Communication, Resources, Disposition, and Bureaucratic Structure. Where the data collection techniques by means of interviews, documentation and observation. Informants and research locations were selected through data presentation techniques, and finally drew conclusions. The results showed that the implementation of the Kotaku program in Kelurahan Talang Jawa focused on development such as the construction of footpaths, drilled wells, drainage and communal toilets running well as expected. This Kotaku program provides many benefits to the community and makes Talang Jawa Village a less slum village. at the planning stage the Kotaku program is designed in such a way that what activities will be carried out later in Kelurahan Talang Jawa, at the survey stage carried out by the Village Facilitator accompanied by an LKM, the funding stage of this program is provided through Provinsi and Kabupaten APBD funds through the Perkim service, and at the implementation stage the implementer is the Kelurahan Talang Jawa Community Self-Help Institution.